For a new socio-pedagogical sustainability at the time of COVID-19. The educational fragility in the perception of teachers and school educator - Zecca, Luisa; Cotza, Valeria (Formazione & insegnamento, 2021)
The paper aims to rethink learning and education from the point of view of social sustainability, looking at the criticalities that emerged during the COVID-19 pandemic from an eco-systemic perspective, which takes the steps from Bronfenbrenner’s ecological theory of human development, in the awareness of the recursive interrelation of the school device with the other levels of the system. In this frame, in the light of the inequalities caused by distance teaching and learning, the need for a new socio-pedagogical sus-tainability that assumes the concept of “educational fragility” emerges, within the theoretical framework of Social Justice Education. Starting from this as-sumption, a qualitative research was developed according to the Student Voice approach, involving 10 students with disabilities or BES and 13 university students active as teachers (both curricular and support) and school ed-ucators, who were able to implement their training through the research. The analysis of the interviews led to present not only an ecological theory of “educational fragility”, but also an overturning of some concepts inherent to the logic of competitiveness, towards a process of resemanticisation that makes explicit the paradigm shift, in the direction of a new sustainability that takes the fragility of the contexts and the school-device as its essential starting point.